Uji Aktivitas Antibakteri Ekstrak Kulit Pisang Muli (Musa acuminata) terhadap Methicillin Resistant Staphylococcus aureus - Lulu Wilda Nurani; Tri Umiana Soleha; Syahrul Hamidi Nasution (CV. Jasa Sukses Abadi, 2020)
MRSA infection is an urgent global health problem. Synthetic or natural antibacterials should be developed as an effort to overcome the problem. The mauli banana peel contains potential antibacterial compounds such as flavonoids, tannins, saponins, alkaloids, and terpenoids. The purpose of this study is to determine the antibacterial activity of mauli banana peel extract (Musa acuminata) against methicillin resistant Staphylococcus aureus (MRSA). The design of this study was true experimental descriptive, with a post-test control group design. This study examined the antibacterial activity of mauli banana peel extract at concentrations of 100%, 50%, 25%, 12.5%, and 6.25% against MRSA bacteria by measuring inhibitory zone, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC). The results of this study showed that mauli banana extract has antibacterial activity against MRSA with the average diameter of inhibition zone ranging from 23,963 mm to 11,075 mm. The MIC obtained at concentrations of 6.25% and MBC at extract with concentration 50%. One-Way Anova test obtained p value = 0,000 (p <0.05) which means there is a significant difference. Based on the experiment, we can conclude that there is antibacterial activity of mauli banana peel extract (Musa acuminata) against methicillin resistant Staphylococcus aureus (MRSA).